Pengaruh Event KapanLagi Korean Festival dan Influencer Terhadap Brand Awareness KapanLagi - Ramadhani, Bayu Rizky; Dianita, Indria Angga (Jurnal Pustaka Komunikasi, 2025)
Competition in the online news media industry continues to increase with technological developments and changes in user behavior. Factors such as brand awareness affect competition between online news media. KapanLagi as an online news media in the entertainment category has innovations in the form of organizing events as a strategy in marketing communication to exist and survive among competitors. KapanLagi organized the KapanLagi Korean Festival 2023 event and used Kimbab Family influencers to increase brand awareness. The research objective is to measure how much influence the KLKF 2023 Event and Influencer Kimbab Family have on KapanLagi Brand Awareness. The method used is quantitative with descriptive research. The research sample amounted to 384 respondents who were taken using probability sampling and simple random sampling techniques. Data analysis used correlation coefficient test, coefficient of determination, multiple linear regression, t test, and f test.  The results stated that the KLKF 2023 Event and Kimbab Family influencers had a positive impact and significant influence on brand awareness. Future research is expected to expand the findings by using other variables in building brand awareness and in different industries.